Vitamin C enhances the in vitro development of early porcine embryos by improving mitochondrial function - Lei Wang; Liu She; Peng Qiu; Meiyun Lv; Yunchuan Zhang; Yunjia Qi; Qin Han; Deshun Shi; Chan Luo (Animal Biotechnology)
Mammalian embryos often suffer from oxidative stress in vitro, as the oxygen in the atmosphere is higher than that in the oviductal environment. Vitamin C (Vc) has been proven to enhance early embryonic development in vitro, but the underlying mechanism remains unclear. In this study, we investigated the pathways of action by which Vc promotes the in vitro development of porcine embryos. Comparative analysis of in vitro and in vivo gene expression profiles of morula found that most of the differentially expressed genes were enriched in pathways related to mitochondrial function. The addition of 12.5 μg/mL Vc to the culture medium significantly increased blastocyst production in a dose- and duration-dependent manner. Moreover, ROS levels were significantly higher in embryos cultured in the air (21% oxygen) than cultured in a hypoxic condition (5% oxygen) and were reduced by Vc supplementation. Vc also significantly increased the mitochondrial membrane potential levels and the expression levels of mitochondrial function-related genes (MFN1 and OPA1) and TCA cycle-related genes (PDHA1 and OGDH) in embryos cultured in vitro. These results suggest that the addition of Vc to the in vitro culture medium can increase the developmental potential and improve the mitochondrial function of early porcine embryos.